P‑Chiral Phosphorus Ligands Based on a 2,3-Dihydrobenzo[d][1,3]oxaphosphole Motif for Asymmetric Catalysis - Xu, Guangqing; Senanayake, Chris H; Tang, Wenjun (Accounts of chemical research, 2019)
Conspectus Despite the rapid progress in the field of asymmetric catalysis, the search for new, efficient, and practical asymmetric catalytic transformations to facilitate the green synthesis of chiral natural products and drugs will continue to be a major ongoing effort in organic chemistry. Chiral phosphorus ligands have played a significant role in recent advances in transition-metal-catalyzed asymmetric transformations. However, there remain numerous challenging issues of reactivity and selectivity in catalysis. The development of new and efficient chiral phosphorus ligands with new structural motifs remains highly desirable. P-Chiral phosphorus ligands have been overlooked and are underdeveloped, except for the early success of DIPAMP, introduced first by Knowles in the early 1970s. It was not until the late 1990s that the development of P-chiral phosphorus ligands regained attention with the advent of bisP*, TangPhos, etc. Nonetheless, most P-chiral phosphorus ligands were either difficult to prepare or operationally inconvenient. The development of efficient, practical, and operationally convenient P-chiral phosphorus ligands with new structural motifs remains an important subject of research. This Account introduces the design and development of a series of practical and efficient P-chiral bis- and monophosphorus ligands based on a 2,3-dihydrobenzo[d][1,3]oxaphosphole motif. Their unique structural and physical properties include conformational unambiguousness, high tunability of electronic and steric properties, and operational simplicity as air-stable solids, which make them practical and exceptional ligands for asymmetric catalysis. Chiral bisphosphorus ligands such as MeO-BIBOP (L3), WingPhos (L4), and iPr-BABIBOP (L7) have demonstrated excellent enantioselectivities and unprecedented turnover numbers (TONs) in various asymmetric hydrogenations and other transformations, providing practical and efficient solutions leading to chiral amines, alcohols, carboxylic acids, and α- and β-amino acids. Chiral biaryl monophosphorus ligands, including BI-DIME (L9), AntPhos (L15), iPr–BI-DIME (L11), etc., have proven to be a class of versatile and powerful ligands for a number of catalytic asymmetric transformations, including asymmetric Suzuki–Miyaura coupling, asymmetric palladium-catalyzed dearomative cyclization, asymmetric hydroboration/diboration, asymmetric nickel-catalyzed reductive coupling, asymmetric palladium-catalyzed intramolecular arylation, asymmetric alkene aryloxyarylation, asymmetric α-arylation, asymmetric Heck reaction, and asymmetric nucleophilic addition, providing efficient solutions leading to various synthetically challenging chiral structures such as chiral biaryls, chiral tertiary alcohols, chiral α-amino tertiary boronic esters, and chiral all-carbon quaternary stereocenters. The high enantioselectivities and TONs obtained with these ligands have resulted in the syntheses of several chiral natural products and therapeutic agents in concise and highly efficient manners. While our efforts on the development of P-chiral phosphorus ligands are ongoing, it should be emphasized that the development of ligands and catalysts with new structural motifs should continue in the search for new reactivity and selectivity to tackle current synthetic challenges. Such effort is destined to promote the advances of asymmetric catalysis as well as synthetic organic chemistry.